2007
DOI: 10.1007/s10461-007-9283-y
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Reports of Condom Use in Thai Couples under Intensive and Regular STI/HIV Risk Reduction Counseling

Abstract: The objective of this study was to determine factors affecting condom use and condom use rates among Thai couples. A cohort of 1,391 reproductive aged women who attended seven family planning clinics in all regions of Thailand and met study eligibility were followed at 3-month intervals for 15-24 months. At each visit, the woman was interviewed about sexual risk behaviors and counseled for sexual risk reduction and condom use. Condoms were provided free of charge. The women were classified into 3 groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…Particularly, laborers were found to be significantly associated with the lowest level of condom use. These results are similar to previous research establishing lower levels of condom use among laborers, farmers, and factory workers [28]. However, among men with casual partners, occupations in sales, service, or labor were associated with increased use of condoms, compared to the professional/technical occupations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Particularly, laborers were found to be significantly associated with the lowest level of condom use. These results are similar to previous research establishing lower levels of condom use among laborers, farmers, and factory workers [28]. However, among men with casual partners, occupations in sales, service, or labor were associated with increased use of condoms, compared to the professional/technical occupations.…”
Section: Discussionsupporting
confidence: 89%
“…The significance of education in explaining condom use patterns has been established by previous research [28], [29]. Similarly, among men with regular partners, being legally married was associated with much lower condom usage, a finding that is consistent with previous research [4], [30], where to use condom use with a regular partner is viewed as an insult to the partner [8] or representing infidelity [30].…”
Section: Discussionsupporting
confidence: 86%
“…While other studies have shown that couples counseling can improve condom-use with the couple dyad participating in the intervention,[ 27 , 28 ] [ 19 21 ] [ 29 ] we believe that this is the first study to demonstrate reductions in HIV risk behaviour among men with regards to other sexual partners. This is particularly important in our setting where formal multiple partner relationships, such as polygynous marriages are common, and involving all partners in these relationships may be logistically challenging.…”
Section: Discussionmentioning
confidence: 79%